A case study for geographical indication of organic milk in Korea using stable isotope ratios-based chemometric analysis. (January 2020) - Chung, Ill-Min; Kim, Jae-Kwang; Yang, Yu-Jin; An, Yeon-Ju; Kim, So-Yeon; Kwon, Chang; Kim, Seung-Hyun
Abstract: This study aimed to examine regional δ 13 C, δ 15 N, δ 18 O, and δ 34 S variations of organic milk in Korea and to develop a differentiation model to identify isotope markers. Herein, δ 13 C, δ 15 N, δ 18 O, and δ 34 S were quantified in organic milk, using a stable isotope ratio mass spectrometer and developed differentiation models through pairwise comparisons using orthogonal projection to latent structure-discriminant analysis, which displayed excellent predictability ( Q 2 cum  ≥ 0.828) among Boryeong, Gochang, and Jeju regions and good predictability ( Q 2 cum  ≥ 0.503) for Hoengseong-related regions. The δ 13 C value was the most important influencer, and the prediction plots by an external validation among Boryeong, Gochang, and Jeju regions accurately predicted the geographical origin of the test milk samples with below 5% of probability of wrong classification. Our results show regional δ 13 C, δ 15 N, δ 18 O, and δ 34 S signatures in Korea, thereby potentially expanding global isotope ratio databases for reliable geographical indication of organic milk. Highlights: Regional δ 13 C, δ 15 N, δ 18 O, and δ 34 S signatures were observed in Korean organic milk. High predictability was seen among Boryeong, Gochang, Jeju, and Hoengseong regions. δ 13 C value was the most important influencer for reliable geographical indication. Models predicted the regional origin as < 5% of probability of wrong classification.